Mechanism of Mitophagy and Its Role in Sepsis Induced Organ Dysfunction: A Review - Zhu, Cheng-long; Yao, Ren-qi; Li, Lu-xi; Li, Peng; Xie, Jian; Wang, Jia-feng; Deng, Xiao-ming (Frontiers in Cell and Developmental Biology, 2021)
Autophagy, an evolutionarily conserved process, plays an important role in maintaining cellular homeostasis under physiological and pathophysiological conditions. It is widely believed that mitochondria influence the development of disease by regulating cellular metabolism. When challenged by different stimuli, mitochondria may experience morphological disorders and functional abnormalities, leading to a selective form of autophagy—mitophagy, which can clear damaged mitochondria to promote mitochondrial quality control. Sepsis is a complex global problem with multiple organ dysfunction, often accompanied by manifold mitochondrial damage. Recent studies have shown that autophagy can regulate both innate and acquired immune processes to protect against organ dysfunction in sepsis. Sepsis-induced mitochondrial dysfunction may play a pathophysiological role in the initiation and progression of sepsis-induced organ failure. Mitophagy is reported to be beneficial for sepsis by eliminating disabled mitochondria and maintaining homeostasis to protect against organ failure. In this review, we summarize the recent findings and mechanisms of mitophagy and its involvement in septic organ dysfunction as a potential therapeutic target.